2013
DOI: 10.1074/jbc.m112.422964
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-converting Enzymes Degrade Intracellular β-Amyloid Produced within the Endosomal/Lysosomal Pathway and Autophagosomes*

Abstract: Background: Endothelin-converting enzymes (ECEs) degrade ␤-amyloid (A␤) peptide. Results: ECE inhibition produces, in addition to extracellular A␤ accumulation, intracellular A␤ accumulation within endosomal/lysosomal and autophagic vesicles. Conclusion: An intracellular pool of A␤ is regulated by ECE activity at the sites of production. Significance: ECE dysfunction may cause intraneuronal A␤ accumulation, which is associated with neurotoxicity early in AD progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 50 publications
(54 reference statements)
4
72
1
Order By: Relevance
“…ECE2 is predominantly localized within the endolysosomal pathway and is responsible for the cleavage of Aβ destined for lysosomal degradation 43. The elevated production of EDN1 may be an unfortunate side effect of over‐activation of this pathway by excessive Aβ42.…”
Section: Discussionmentioning
confidence: 99%
“…ECE2 is predominantly localized within the endolysosomal pathway and is responsible for the cleavage of Aβ destined for lysosomal degradation 43. The elevated production of EDN1 may be an unfortunate side effect of over‐activation of this pathway by excessive Aβ42.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that in spite of the elevation of both peptide and copper ion concentrations during the ionization process than in the incubation buffer, the ratio between the copper ion and Aβ(1-16) would be fixed even after evaporation of the solvent as shown by other studies. 12,22 Moreover, since there is an increase in the copper content of Cu 2+ -Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) complexes from fractions with higher copper to peptide ratios, this would suggest that the metal was attached to the peptide prior to ESI-MS analysis. We demonstrate here that Aβ(1-16) is able to bind up to three Cu 2+ ions at pH 7.4, and up to four Cu 2+ ions when the pH value decreased to 6.6.…”
Section: Resultsmentioning
confidence: 99%
“…Copper binding to Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) peptide. Using ESI-MS, we found that the binding of Cu : peptide molar ratio was 10:1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations